2001
DOI: 10.1021/la010846w
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of the Adsorption Equilibrium of a Model Surfactant Solution on Hydrophilic Solid Surfaces

Abstract: We performed Monte Carlo simulations to study the adsorption behavior of a small flexible model surfactant on hydrophilic surfaces. A coarse-grained lattice model was used to account for excluded-volume effects and nearest-neighbor interactions. The model predicts adsorption isotherms that agree qualitatively with experimental results. The results of the simulation complete and support experimental structure investigations made with AFM, ellipsometry, and neutron reflectometry. Adsorbed bilayer structures depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…The bottom of the simulation box at z = 0 represents a smooth hydrophilic surface, while the upper surface of box at z = 121 is an impenetrable wall made of water site [37]. As is described above, the box has three distinct regions: the control zone, the diffusion zone and the solid surface.…”
Section: Models and Methodsmentioning
confidence: 98%
“…The bottom of the simulation box at z = 0 represents a smooth hydrophilic surface, while the upper surface of box at z = 121 is an impenetrable wall made of water site [37]. As is described above, the box has three distinct regions: the control zone, the diffusion zone and the solid surface.…”
Section: Models and Methodsmentioning
confidence: 98%
“…[1][2][3][4][5][6][7] To describe surfactant self-assembly, the relationship between surfactant properties, surface characteristics, and adsorption thermodynamics must be understood. Many interesting experimental [8][9][10][11][12][13] and computational [14][15][16][17][18][19][20][21][22] results concerning surfactant adsorption on flat homogeneous surfaces have been reported in the literature. However, very little has been carefully quantified regarding surfactant adsorption on heterogeneous surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation has also been used to understand the adsorption mechanisms and the geometry of the surfactant aggregates on hydrophilic [30][31][32][33], hydrophobic [34][35][36][37][38][39][40][41] and heterogeneous [42,43] surfaces. Using lattice Monte Carlo simulations Wijmans and Linse [37] have shown that the surfactants adsorb first as free molecules or as patches, then at higher concentrations as monolayers.…”
Section: Introductionmentioning
confidence: 99%